Borrowing Spaces: The Geographies of 'Libraries of Things' in the Canadian Sharing Economy. (22nd February 2023) - Lynch, Nicholas
Abstract: Over the last decade, the sharing economy has resulted in numerous innovative sharing and borrowing practices, many of which have the potential to radically transform communities and societies. One such innovation is the Library of Things (LoT), a non‐profit sharing space modelled on traditional library systems, which enables users to borrow a diverse range of equipment, tools and goods. This paper contributes to the emerging literature and research on the non‐profit sharing economy and the role of LoTs as sharing spaces. Drawing on in‐depth interviews with LoT founders and managers, three main socio‐spatial themes are discussed in the development of Canadian LoTs: sharing cultures, sharing capital and sharing politics. Overall, this work highlights that the success and sustainability of these sharing spaces hinge on the negotiation of these complex social and spatial dynamics, ranging from their capacity to build spaces of collaboration, experimentation and community. Abstract : The Toronto Tool Library: a vital sharing space and Library of Things in the heart of Canada's largest city (photo by Tool_Library; https://creativecommons.org/licenses/by/2.0/?ref=openverse.)